Development of Science Learning Material Based on Scientific Literacy on Plants Tissues' Structure and Function Topic - Nor' ainah; Yudha Irhasyuarna; Mella Mutika Sari (Indonesian Journal of Science Education and Applied Science, 2023)
Scientific literacy is knowledge and skills in the bolawins scientific field in order to have the ability to identify problems, gain new insights, explain scientific phenomena, make conclusions according to reality, master the uniqueness of science, be aware of science and technology that shape the natural environment, and be willing to participate and care with problems related to science. The Science module is teaching material in science lessons that can make it easier to achieve learning objectives. Teaching materials used in the learning process have an important role in determining the success of learning. Teaching materials used in SMP/MTs tend not to involve students in exploring and applying concepts, causing them to be less active and creative in the learning process. Therefore, researchers through this research developed a scientific literacy-based teaching material related to the structure and function of plant tissue in natural science lessons. This study aims to explain the feasibility of scientific literacy-based teaching materials in the form of modules, their uses, and their practicality. This research is classified as development research. The development model used is the 4D model (Define, Design, Development, and Dissemination). The results showed that the validity of the module obtained a percentage of 90% with an average of 3.60 valid criteria without revision. Then the results of the module scientific literacy validity obtained a percentage of 80% with an average of 3.37 valid criteria. So it can be concluded that the modules used as science teaching materials based on scientific literacy on the structure and function of plant tissues are valid and suitable for use as teaching materials.